Energy harvesting from electromagnetic radiation - Nur Iskandar, Hamzah (2016)
The focus of this work is on the harvesting the energy via electromagnetic radiation. The energy harvesting energy device consists of two main subsystems. The first subsystem is the receiving antenna that responsible to capture all the RF surrounding and later it will convert into DC output. The second subsystem is rectifier system or a charge pump, it can convert the RF as an input power into DC output power and it pump is design by modifying voltage multiplier which consists of diodes and capacitors. The antenna can transmit and receive the energy through the air from the current in the form of electromagnetic waves which is radio waves at several operating frequency. In this project, coil antenna also known as spring antenna to be the receiver antenna for the system. In theory, it can produce an output which is multiple from the input power supply depends on the stages used. The higher the frequency, the higher the output can be produced. Besides that, the amount of frequency can be harvested based on the size and the range of the frequency that can be absorbed by the antenna.